A Review on Banana Fiber and Its Properties - Kavitha, V.; G, Aparna (Asian Journal of Pharmaceutical Research and Development, 2021)
There are many types of natural fiber including hemp, flax, jute, wood fiber, rice husks, straw wheat, oats, bagasse, barley, grass reeds, banana fiber, oil palm empty fruit bunch, coir, sisal, cotton, kenaf, ramie, water pennywort, paper-mulberry, kapok, abaca, pineapple leaf fiber. The production of banana in India is 13.5 million tons per annual. Banana forming generates more quantity of biomass which goes as waste. The above ground parts like pseudo-stem and peduncle are the major source of fiber. Banana fiber used as a raw material in industry for production of papers, tea bags, currency and reinforced as a polymer composite. Natural fiber is used as an alternative resource to synthetic fibers as well as reinforcement for polymer composite materials and the manufacturing is inexpensive, renewable and environment friendly. Natural fibers have low cost, low density and low durability as compare to synthetic fibers but with the help of fiber treatments, mechanical properties of natural fibers are improved. In this paper, banana fibers are compared through their applications, use and properties and thus it is concluded that the banana fibers provide better chemical composition and properties.